Methodological problems of the social sciences. Misunderstandings and clarifications - Fusari, A. (Archives of Business Research, 2018)
Growing technological changes and innovation make it increasingly difficult to understand the course of social reality, while the intensification of the relations between different regions of the Earth and the power achieved by financial capital on a world scale amplify the dimensions and visibility of disequilibria and iniquities, and sharpen frustration and sentiments of insecurity. The roots of this theoretical and practical confusion are identified, in our paper for submission, with the adoption within the social sciences of the method of observation and verification. This may seem surprising in the light of the fact that the triumph of this method facilitated the emergence of the modern natural (and mechanical) sciences. And in fact, just this success has propelled the extension of the observation-verification method into the social sciences, where it is today dominant. The deficiencies of this method in the analysis of social reality are, however, masked by the trappings of scientific rigour imparted, which is often enhanced by additional borrowing of method from the mathematical and formal sciences. It must be recognized that the observation-verification works well when applied to quasi-stationary societies, where the key hypothesis of the repetitiveness (or quasi-repetitiveness) of events typical of the natural sciences and the corresponding method is fulfilled. But with the advent of modern dynamic society, itself very much an effect of the great advancement of the natural and formal sciences, the failure of the methodologies of these sciences with regard to the analysis of social reality has become increasingly marked and its consequences ever more devastating. My book Methodological Misconceptions in the Social Sciences, Springer 2014, was dedicated to an accurate analysis of this embarrassing situation and a consideration of ways to remedy it. The most efficacious way to meet this fleeting social reality seems to be to scientifically highlight basic institutions, economic behaviour and values with their steady changes caused by the accumulation of creative and choice processes. In doing so, long-run trends can be explored in order to understand and manage the disequilibrating-reequilibrating motion characterizing the life of dynamic societies.